REAKSI PASAR MODAL INDONESIA (BEI) TERHADAP RESHUFFLE KABINET - Uke Prajogo (Universitas PGRI Madiun, 2013)
The capital market is one of the important financial sector in the economy of a country. The capital market is one of the effective means to facilitate long-term funds held by the public to be channeled in productive sectors. Capital market as one of the economic instruments is influenced by events that contain information for investors. In- creasingly important role of capital markets in the economy of a country, the more sensi- tive the capital market to various events around him. This study aims to assess the capital market reaction to the announcement of United Indonesia Cabinet reshuffle vol 2 which took place on October 19, 2011. This research is quantitative descriptive. Assessment Cabinet Reshuffle reaction to the announcement of the stock price movement LQ45 done through observation of price movements, abnormal returns (abnormal returns), Capital Asset Pricing Model (CAPM), and to Varibility Reward Ratio (RV) during the observa- tion period of 14 days before and 14 days after the announcement date. The results showed that the announcement of the cabinet reshuffle, do not give too strong an influence on the movement of stock prices, this is evidenced in the average stock price and the average abnormal return is experiencing fluctuating movements in the period of United Indonesia Cabinet reshuffle Volume 2. There is no visible trend of the market overreacted to the emergence of a significant price fall or rise significantly. Based on this, there is no sig- nificantrelationship between abnormal returns before and after the cabinet reshuffle which was conducted on October 19, 2011. Pessimistic attitude toward improved market per- formance of the post-reshuffle cabinet ministers are also an indication that the market is not overl action resulted in the announcement of the overnment's cabinet reshuffle. This study also showed that agriculture, mining, and chemical industry base, a variety of industries, finance and trade in services and investment sector was the most good for investment because of the calculation CAPM expected return E (Ri) produced smaller than the average expected return is realized (Av.Ri) per sector and the low share price means the right time to invest. For Industrial and Chemical sector is a sector that is at the top rank has a value of -0.15987 and is the most affected sectors. While a good stock for investment is INTP, SMGR, KRAS, and CPIN. Top ranked stocks are INTP that has the highest value that is equal to -0.09966 and is the most affected stocks.